Analisa Keasaman dan Total Bakteri Asam Laktat Yogurt Akibat Bahan Baku dan Persentase Lactobacillus casei yang Berbeda - Yusdar Zakaria; Yurliasni Yurliasni; Mira Delima; Ely Diana (Agricultural Faculty, 2013)
Analyze of acidity and amount of lactic acid bacteria of yogurt made from different milk types and lactobacillus casei percentageABSTRACT. The objective of this experiment is to determine the effect of milk types and percentages of Lactobacillus casei as a starter to the amount of Lactic Acid Bacteria in yogurt and its pH value and Lactic Acid value. Factorial Completely Randomized Design with two factors and three replications was applied. The A factor was the milk types that were a1 = Powder Milk, a2 = Fresh Milk and a3 = UHT milk. The B factor was the percentages of Lactobacillus casei (b1 = 5% and b2 = 10%). Parameters observed were the level of lactic acid, the pH value of yogurt and the amount of lactic acid bacteria. The result showed significantly difference (P0.01) from the use of milk types and Lactobacillus casei percentages on the lactic acid level, and there are no interaction between factors. There was also significant different (P0.01) showed from pH value and an interaction between both factors was presented. In addition there was significant difference (P0.05) showed by the amount of lactic acid bacteria, and an interaction between both factors was also existed. The research concluded that the higher the percentage of starter, the higher the level of lactic acid and the amount of lactic acid bacteria of yogurt that made from all milk types. On the contrary, the higher the percentage of starter, the lower the pH value of yogurt.